An Integration Avenue of Ground Monitoring Based on Wireless Sensor Networks. (31st December 2013) - Kim, Young-Joo; Hong, Sungmin; Lee, Jong-uk; Song, Sejun; Kim, Daeyoung
Abstract : Since wireless sensor networks (WSNs) have a lot of potential capability to provide diverse services to human by monitoring things scattered in real world, they are envisioned as one of the core enabling technologies for ubiquitous computing which organizes and mediates both physical and social interactions anytime and anywhere. WSNs are being adopted in various fields and things in their zones are being monitored. However, existing WSNs are normally designed for observing special zones or regional things based on small-scale, low power, and short range technologies. Seamless system integration at a global scale is still in its infancy stage due to the lack of the fundamental integration technologies. In this paper, we present a global integration avenue of ground monitoring based on WSNs. The proposed avenue includes design, integration, and operational strategies of IP-WSN based territorial monitoring system to ensure compatibility, interoperability, and real-time. Specifically, we offer the standardization of sensing data formats using IP-WSN and database interfaces using EPC sensor network, which enable a spontaneous and systematic integration among the legacy WSN systems. Also, we categorize network topology according to topographic characteristics thereby helping deploy sensor nodes on the real environment. Therefore, the proposed technology would be a milestone for the practically deployable global territorial monitoring systems.